2018
DOI: 10.1097/qai.0000000000001819
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Comprehensive Adolescent-Focused Case Finding Intervention on Uptake of HIV Testing and Linkage to Care Among Adolescents in Western Kenya

Abstract: Background:Low HIV testing uptake prevents identification of adolescents living with HIV and linkage to care and treatment. We implemented an innovative service package at health care facilities to improve HIV testing uptake and linkage to care among adolescents aged 10–19 years in Western Kenya.Methods:This quasi-experimental study used preintervention and postintervention data at 139 health care facilities (hospitals, health centers, and dispensaries). The package included health worker capacity building, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…The increasing proportion of HIV tests offered through MC observed in the study reflects an attempt of the Zambian government to reach underserved and hard-to-reach youth. In addition to the latter, other community-based strategies that are specific to youth should be explored given their promising results, such as adolescent-focused case finding implemented in Kenya and home-based HTC [ 48 , 49 ]. HIV self-testing (HST) is also part of interventions in Zambia and has shown some acceptance and the potential to improve access to HIV testing [ 50 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing proportion of HIV tests offered through MC observed in the study reflects an attempt of the Zambian government to reach underserved and hard-to-reach youth. In addition to the latter, other community-based strategies that are specific to youth should be explored given their promising results, such as adolescent-focused case finding implemented in Kenya and home-based HTC [ 48 , 49 ]. HIV self-testing (HST) is also part of interventions in Zambia and has shown some acceptance and the potential to improve access to HIV testing [ 50 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health services become unavailable to students when clinic opening hours coincide with lecture hours, or when clinics are not open during weekends and public holidays. Other studies have shown that the inclusion of extended clinic hours, after-hours, and over weekends, in a comprehensive package of services improves uptake and linkage to care among adolescents [ 9 , 12 , 35 , 37 ]. It is not clear why more females than males in our study perceived the inability to leave/stay away from studies as a potential barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Health services can be made more accessible to adolescents and more "youth-friendly" by a variety of approaches, including staff training, stigma reduction, adapting opening hours, shortening waiting times, offering psychosocial support, and peer support groups, that improve HIV testing uptake and treatment outcomes among adolescents and that provide services related to sexual and reproductive and mental health (106)(107)(108)(109)(110)(111)(112)(113)(114).…”
Section: Ensure Availability Of Commodities For Early Diagnosis and Omentioning
confidence: 99%